Enhancement of state response capability and famine mitigation: a comparative analysis of two drought events in northern China during the Ming dynasty - F. Tian; F. Tian; Y. Su; Y. Su; X. Chen; X. Chen; L. Tao; L. Tao (Natural Hazards and Earth System Sciences)
Studying social impacts of and responses to historical extreme climate events can offer valuable insights into coping with major disaster events and adapting to climate change better. This paper developed a model of the processes and responses to extreme drought-induced famines in ancient China. Based on this, the study explored the differences in famine causation and response effectiveness between the Chenghua drought (1483–1486 CE) and Wanli drought (1585–1588 CE). The findings are as follows: (1) by the time of the Wanli drought, the increase in land reclamation had enhanced societal defence, preventing many drought-affected counties from experiencing famine. Even in cases where famines did occur, their severity was lower than during the Chenghua drought. (2) State emergency measures, including exemption and relief, proved effective in mitigating famines. The stronger finance and economy during the Wanli drought enabled more robust relief efforts, resulting in lower famine severity. (3) Famine response capabilities varied regionally. Shandong, Beijing, Tianjin, and Hebei demonstrated strong defensive capabilities and effective state emergency responses, while Shanxi had weaker defensive abilities, making it more vulnerable to famine. The defensive capabilities in Henan, Shaanxi, Gansu, and Ningxia showed significant improvement.